P49 Does valsalva manoeuvre reduce the risk of complications in CT-guided lung biopsies?. (15th November 2016) - Syed, AE; Syed, I; Ahmed, R; Parvu, O; Pancione, L; Alvi, A; Novacic, K; Akram, R
Abstract : Introduction: Multiple complications in CT-guided lung biopsy have been described with pneumothorax known to be the commonest. 1 This often leads to patients being admitted to hospital for observation or even drainage. We hypothesised that increased intrathoracic pressure may reduce complications and a comparative retrospective cohort study was performed with the types and rates of complications recorded in patients instructed to perform a Valsalva manoeuvre versus those who were not. Methods: Patients who underwent CT-guided lung or pleural biopsies performed by multiple operators between January 2005 and December 2014 at Queens Hospital, Essex, UK, were retrospectively identified. Information from RIS reports and images from PACS were analysed. Patients were stratified into two groups, those who undertook Valsalva at time of biopsy and those who did not. Complication rates were assessed for haemoptysis, haemothorax and pneumothoraces including those requiring chest drain insertion. Statistical analysis was performed using Chi square test. Results: 791 procedures were performed over 10 years, 420 patients undertook Valsalva manoeuvre with mean ages 70.1 years ±SD 12.54: range 21–93. The other 371 patients did not undertake a Valsalva manoeuvre. Their mean ages were 71.1 years ±SD 11.52: range 27–91. In total, 119 patients had complications post-procedure: 64 in the non-Valsalva group vs 55 in the Valsalva group (17.25% vs 13.10%, p = 0.05). Rates of haemoptysis were significantly reduced with Valsalva (2.16% vs 0.24%, p = 0.006). Pneumothorax requiring chest drain (2.70% vs 1.43%, p = 0.10) and those managed conservatively (12.40% vs 11.19%, p = 0.30) were higher in the non-Valsalva group. Rate of haemothorax (0.24% vs 0%, p = 1) was greater in the Valsalva group. Conclusion: Our study shows that Valsalva manoeuvre at the time of biopsy helps reduce the rate of complications, with a statistically significant decrease in rate of haemoptysis. Rates of pneumothoraces requiring chest drain insertion and other pneumothoraces were also reduced. The differences could be explained by physiological changes in pulmonary wedge pressure and positive end expiratory pressure brought about by increased intrathoracic pressure following Valsalva manoeuvre. Reference: Manhire A, Charig M, Clelland C, et al . Guidelines for radiologically guided lung biopsy. British thoracic society guidelines. Thorax 2003;58 :920–936.